Small Molecule Sequestration of the Intrinsically Disordered Protein, p27Kip1, Within Soluble Oligomers. Issue 18 (3rd September 2021) - Iconaru, Luigi I.; Das, Sourav; Nourse, Amanda; Shelat, Anang A.; Zuo, Jian; Kriwacki, Richard W.
Graphical abstract: Highlights: Due to their lack of stable structure, IDPs are often considered 'undruggable' A multivalent small molecule binds clusters of aromatic residues within p27, an IDP. These small molecules sequester p27 within soluble oligomers. Both hydrophobic and polar moieties mediate these small molecule/IDP interactions. We propose sequestration within soluble oligomers as a strategy of drugging IDPs. Abstract: Proteins that exhibit intrinsically disordered regions (IDRs) are prevalent in the human proteome and perform diverse biological functions, including signaling and regulation. Due to these important roles, misregulation of intrinsically disordered proteins (IDPs) is associated with myriad human diseases, including neurodegeneration and cancer. The inherent flexibility of IDPs limits the applicability of the traditional structure-based drug design paradigm; therefore, IDPs have long been considered "undruggable". Using NMR spectroscopy and other methods, we previously discovered small, drug-like molecules that bind specifically, albeit weakly, to dynamic clusters of aromatic residues within p27 Kip1 (p27), an archetypal disordered protein involved in cell cycle regulation. Here, using synthetic chemistry, NMR spectroscopy and other biophysical methods, we discovered elaborated analogs of our previously reported molecules with 30-fold increased affinity for p27 (apparent Kd = 57 ± 19 μM). Strikingly, using analytical ultracentrifugation methods, we showed that the highest affinity compounds caused p27 to form soluble, disordered oligomers. Based on these observations, we propose that sequestration within soluble oligomers may represent a general strategy for therapeutically targeting disease-associated IDPs in the future.